A plasma biomarker panel for detecting early amyloid-β accumulation and its changes in middle-aged cognitively unimpaired individuals at risk for Alzheimer’s diseaseResearch in context - Armand González-Escalante; Marta Milà-Alomà; Wagner S. Brum; Nicholas J. Ashton; Paula Ortiz-Romero; Mahnaz Shekari; Marta del Campo; Federica Anastasi; Clara Quijano-Rubio; Gwendlyn Kollmorgen; Carolina Minguillón; Gonzalo Sánchez-Benavides; et al. (EBioMedicine)
Summary: Background: Plasma biomarkers of Alzheimer’s disease (AD) change during preclinical stages, indicating potential for detecting amyloid-β (Aβ) pathology in cognitively unimpaired (CU) individuals. Given the need for accurate, scalable biomarkers, we evaluated a fully automated plasma panel to detect and monitor longitudinal Aβ accumulation in CU individuals. Methods: In this longitudinal study, we examined a plasma panel (Aβ42/40, p-tau181, GFAP, NfL, p-tau217 and ApoE4) in CU participants at risk for AD. We assessed the biomarkers’ performance to detect Aβ pathology and the cross-sectional and longitudinal relationships between the biomarkers and Aβ accumulation, neurodegeneration and cognition. Findings: We included 400 middle-aged CU participants, of whom 135 (33.8%) were CSF Aβ-positive. All plasma biomarkers differed between Aβ-positive and -negative individuals, with plasma Aβ42/40, p-tau217, p-tau181/Aβ42, and p-tau217/Aβ42 showing the best performance in detecting A+ CU individuals. However, plasma Aβ42/40 was sensitive to random variability. Plasma p-tau217/Aβ42 had the highest performance in detecting PET A+ individuals (AUC = 0.94). All baseline plasma biomarkers were associated with longitudinal increases in Aβ deposition (mean follow-up [SD]: 3.27 ± 0.5). Longitudinal changes in plasma p-tau217 and p-tau217/Aβ42 were associated with concurrent changes in Aβ (both CSF and PET) and soluble tau pathology. Interpretation: In CU individuals, several plasma biomarkers at baseline detect Aβ accumulation and are associated with its short-term change. Plasma p-tau217, and p-tau217/Aβ42 longitudinal changes reflect concurrent Aβ accumulation during this period. These findings help enrich studies in CU individuals at risk of progressing to AD. Funding: ERC-2020-STG (Grant agreement No. 948677); ERA PerMed-ERA NET and the Generalitat de Catalunya (SLD077/21/000001); PI19/00155; PI22/00456, LCF/BQ/PR21/11840004.